Research tools for design. Spatial layout and patterns of users' behaviour Proceedings of Seminar, 28-29 January 2010, Department of Architectural Technology and Design "P. Spadolini", University of Florence - SETOLA, NICOLETTA (Proceedings e report, 2011)
The publication proposes a critical reading of the results emerging from the Seminar organised in January 2010 by the Department of Architectural and Design Technology on research tools for the architectural project. The spatial layout of buildings and urban spaces influences behaviour and the relations of the users, and in this displays the social nature of the architectural function in comparison to other spheres of design. Space Syntax (theory, methodology and techniques for the analysis of complex systems) takes this theory as the basis for its research. The seminar, attended by leading academic and professional figures, offered the opportunity for exchange between its own research and the experiences carried forward by the Space Syntax research and consultancy group.